(untitled) (Italian Review of Legal History, 2024)
The terms «spartenza» and «restanza» not only define two complementary experiences linked to the migratory phenomenon, (departing and remaining), but highlight the common legal identity of the so-called «middle people», suspended between flight and seclusion, between lost rights and statuses and others not yet acquired, who perceive themselves in any case and everywhere «out of place»: a «legal minority» whose denunciation emerges from a substantial popular literature, the so called «spartenza songs» capable of eliciting responses from below and overcoming the stigma by recovering the lost identity.